'If they are going to university, they are gonna need a language GCSE': Co-constructing the social divide in language learning in England. (August 2018) - Lanvers, Ursula
Abstract: The last decade has seen increasing evidence from the UK on the social divide in language learning. To date, there are no studies that relate the views of school stakeholders (senior management, language teachers, students) on modern languages to actual language policy in individual schools, and the socio-economic characteristics of the schools themselves. This article reports on interviews and focus groups conducted in four schools in north England, an area with below (national) average uptake of language learning beyond the compulsory age. In each school, focus groups with students (aged 13/14), and interviews with language teachers and senior management were undertaken. The data was analysed using thematic analysis, and corpus linguistics. Results reveal that students from all school types, including in areas of strong deprivation, rate and value languages. School management, however, may articulate a wide range of possible rationales for languages, but tend to justify their own language policies, citing performance-driven pressures, the academic and social background of their schools' intake, and the purported professional aspirations of their students. In this manner, school management teams shape opportunities to learn languages based on the socio-economic characteristics of their intake and contribute to the social divide in language learning in England.